La economía mundial y América Latina : reflexiones sobre el corto y el mediano plazo - Tomassini, Luciano (Estudios Internacionales, 1985)
In this paper, an analysis is carried out on the economic perspectives of Latin America up to the end of the eighties, the considerations on the evolution of the industrialized countries and that of the Latin American countries, as well as on the short and medium term. We hold that all of these are inextricably linked. However, it is estimated that the factors linked to the evolution of the industrialized world and the alternatives proposed in the medium term constitute the most important elements of judgment to anticipate or guide the evolution of the Latin American economies, and this conviction is reflected in the analysis. First, the situation of the industrialized countries is examined and then that of the Latin American countries. In both cases, progress is made from the long to the short term. At the end some considerations about the future are formulated.